On carbon distribution in austenite Fe‑C alloys - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
Based on the calculations of the model of the elementary crystal cell γ‑iron, it is shown that carbon ions cannot be present in its open pores. Carbon in Fe‑C alloys dissolves and distributes mainly as elementary graphite nanocrystals. In steel austenite, carbon is found in elementary graphite nanocrystals and in iron‑carbon complexes. In cast iron austenite, carbon is found in elementary graphite nanocrystals.